The rehabilitation of the patient’s new physiology after a bariatric surgery (Research, Society and Development, 2023)
Bariatric surgery is a procedure recommended for the treatment of obesity, promoting a better wellbeing for the patient who is submitted to such surgical intervention, when clinical intervention is not successful. This surgery causes many changes in the patient’s physiology, especially gastrointestinal and, because of that, there are rigorous indication criteria in order to be performed. The present revision aimed to understand those physiological changes, focusing on the remission of chronic diseases e microbiota alterations, apart from identifying the main characteristics that lead to the recommendation for the procedure. A bibliographic search was conducted in the PubMed and Scielo databases, through an systematic literature review, of publications from 2017 to 2022, written in Portuguese, English and Spanish. Hence, bariatric surgery promotes significant physiological changes on the patient after the procedure, in the chronic diseases aspect as well as in the gastrointestinal microbiota.